A presença de estudantes com deficiência física e visual no curso de Educação Física da Universidade Federal do Ceará: questões (im)postas à avaliação da aprendizagem - Torres, Michele Gonçalves Romcy (2020)
This study aims to comprehend the learning evaluation and social inclusion with the disability students enrolled the Physical Education course at Physical Education and Sports Institute (IEFES) of Federal University of Ceara (UFC). The study still intends to: I) to identify evaluation procedures used by professors with these handicap students from IEFES: II) to map suggestions from professors and students for a inclusive practice of learning evaluation; III) to codify and analyze the proposals for these ones evaluation at the Phisical Education undergraduation, composing a validation process of the collected material. The Theoretical Reference adopted is based, mainly, on the ideas of Hadji (2001); Hoffmann (2005, 2006); Luckesi (1995, 1999, 2005, 2011); Stake (1975,1983) regarding the learning evaluation; and Mantoan (2003, 2010) e Lustosa (2009, 2017) regarding the inclusion of people with disabilities, besides the discussion about the principles of an evaluation that is inclusive with regard to higher education. For this purpose, it was made a qualitative research, in the form of a case study. The sample was composed by 13 subjects, in total, 4 students, two with physical disability and two with visual deficiency, enrolled at IEFES/UFC and 9 professors, one of whom is director of the Institute. The data collection instruments used were the semi structured interview for the students and the structured interview for the professors, applied in november 2019. Data analysis shows that there are no adaptations to assess students with disabilities. Professors believe that the way they evaluate, is appropriate for all students, despite it was not verified such finding in the speeches of the academic target audience of such practices. Another important finding refers to the barriers faced by disabled students during their formative process, which certainly does not give the same opportunities of access to the curriculum that benefits other students. It was found, on the other hand, that changes made on teaching and institutional practices are still very incipient related to what would be necessary o inclusive procedures in fact, configured only by the use of computers and help from someone in order to read for the visual deficiency students. In this sense, the professors also show as demands arising from the process of inclusion in education that they be informed in advance about the attendance of disability students in their classrooms, so they can effect pedagogical strategies and prepare themselves to attend this students at the university. This study shows, therefore, a list of shortages and gaps relevant to the two segments (professors and students), that is, not being found none of process actor satisfied with their needs, emerging, in its turn, suggestions and indicators about what should be done at a University that excels in a teaching for everyone and ulfills its social function.